Analysis of Artificial Narrow Intelligence (Ani) in the Indian Retail and E-Commerce Sector (British Journal of Multidisciplinary and Advanced Studies, 2025)
The study examines how artificial narrow intelligence innovation affect India’s retail and e-commerce industries with an emphasis on operational enhancement, moral issues and consumer satisfaction. Key parameters such as viability of chatbots interactions, suggestion precision, timeframe improvements for complaint settlement, frequency of consumer interactions, privacy related issue rate and permission level for utilizing information were examined via survey of 406 respondents. The real-world application and perks of artificial intelligence are demonstrated through Flipkart, Reliance Retail, Big Basket, Myntra and Tata Cliq. These investigations emphasize improvement in consumer experience, commitment and productivity and decrease in fraud and cost associated with inventory. The study proposes goals and theories to direct future research while identifying knowledge gaps in client responses, measuring client contentment, ethical considerations and regulatory effects. The result indicates that while ANI technologies greatly improve operational effectiveness and consumer happiness, more work needs to be done to deal with privacy and unethical practices. To promote safe and efficient implementation of ANI, important recommendations involve strengthening openness in ANI techniques, putting in place strong information securities safeguard and encouraging industry players and law enforcement agencies to collaborate.